Comparison of the in vitro protein digestibility of Protaetia brevitarsis larvae and beef loin before and after defatting. (15th February 2021) - Lee, Seonmin; Jo, Kyung; Yong, Hae In; Choi, Yun-Sang; Jung, Samooel
Highlights: In vitro protein digestibility of Protaetia brevitarsis larvae was evaluated. Larvae and beef proteins had different molecular distribution. Digesta of larvae had significantly more proteins under 3 and 10 kDa than beef. Defatting with hexane improved digestive accessibility to actin in larvae. P. brevitarsis larvae with great digestibility can be a substitute for beef protein. Abstract: Protein digestibility of Protaetia brevitarsis larvae before and after defatting by hexane was compared with that of beef loin in an in vitro digestion model. Larvae had higher crude protein content and 10% trichloroacetic acid (10% TCA)-soluble α-amino groups than beef. Decreases in the levels of total free sulfhydryl groups and 10% TCA-soluble α-amino groups were detected in larvae and beef after defatting ( P < 0.05 ). Surface hydrophobicity increased after defatting in both larvae and beef, ( P < 0.05 ) and tryptophan fluorescence intensity decreased in defatted larvae but increased in defatted beef. Levels of proteins digested into sizes under 3 and 10 kDa in larvae were higher than those in beef ( P < 0.05 ), and defatting did not induce an effect in larvae. Therefore, in the aspect of high protein content and digestibility, larvae of P. brevitarsis can be a potential substitute of animal proteins.